ANALISA VARIASI ARUS PENGELASAN SS 304 MENGGUNAKAN SHIELDED METAL ARC WELDING (SMAW) TERHADAP KEKUATAN MEKANISNYA - Nidia Lestari (Otopro, 2020)
Austenitic stainless steel or commonly known as AISI 304 stainless steel has advantages, including good ductility at relatively low temperatures and high resistance to corrosion. These properties make Austenitic Stainless Steel a candidate material for use in pipe fabrication systems, automotive exhaust gas systems and some equipment related to the chemical and nuclear industry. Therefore, it is necessary to analyze the variation of welding currents on the strength of the welds in the application of Shielded Metal Arc Welding (SMAW) on stainless steel. The electrodes used are E308-16 types with current variations of 90 amperes, 100 amperes and 110 amperes. The results showed that the electric current factor in the SMAW welding process greatly influenced the welding results in terms of its strength. The highest mechanical strength was obtained at welding current of 110 Ampere, with a heat input of 976.067 J / mm, an average mechanical strength of 68.438 kg / mm2 for tensile stress and strain of 47.451% in the tensile test, and an average value of hardness of 225.008 HV for hardness test in weld.